Eﬀect of Art Therapy on Changes in Psycho-Emotional State for Women Who Have Attempted Suicide - Stanislovas Mostauskis; Aušra Sebeikaitė; Jolita Rapolienė (Lithuanian Sports University, 2023)
Background. Research is directed towards female suicides and the solution of the postvention problems in Lithuania. Suicidal behavior of women is conditioned by their psychological  sensitivity to different psycho-social factors. The-psycho-emotional state of women who have attempted suicide is worsened, different negative emotions prevail, they lack self-esteem  and are disappointed. The methods used in the research aim to answer the same question: does art therapy have an effect on the psycho-emotional state of women who have attempted suicide?  It uses different methods of data analysis, i.e. quantitative and qualitative analysis of a small sample. Research aim. The aim of the research is to present effects of art therapy on changes in the psycho-emotional state of women who have attempted suicide. The aim of the research is supported by the following tasks and questions. Tasks:  1) to determine changes of depression symptoms; 2) to determine change of anxiety symptoms. Questions: 1) how do visually dominant iconographic motifs in patients' drawings change during art therapy? 2) how do visually dominant formal motifs in patients' drawings change during art therapy? 3) does the change of iconographic and formal motifs relate to changes of the emotional state of a selected group of women? 4) how interrelated are results of quantitative and qualitative research methods? Methods. Mixed research was conducted using the HADS scale, with analysis of visually dominant iconographic and formal elements. Results. The art therapy intervention significantly reduced the level of depression in the subjects. Art therapy had no significant effect on subjects' anxiety levels. Selected iconographic motifs in the subjectsʼ drawings during the process of art therapy changed: from visually unindentifiable to recognizable objects; from an abstract symbolic meaning to a more concrete and clearly defined meaning; from a smaller to a larger number of iconographic elements; from an iconographically blurred to a more explicit plot. Selected formal motifs in the patients' drawings during the process of art therapy changed: from incomplete to more detailed depiction of the object; from closed to more open silhouette type; from an isolated object opposed to the surrounding space to an object increasingly infiltrating into that space; from a closed to a progressively more open composition; from linearity to pictoriality; from darker to lighter color scale; from poorer to richer color palettes. The change of iconographic and formal motifs is related to the change of the emotional state of the subjects: the reduced isolation of the depicted objects and the strict separation from the surrounding space show a reduced opposition of the subjects, and the beginning of  the social and psychological connection with the surrounding world. The shift from an incomplete to a more detailed depiction of an object shows that the former uncontrollability of the subjects' self, their feelings, and their connection with the environment turns into clear and rational controllability; more concrete and realistic drawings show the increased awareness of the subjects and better connection with the surrounding world. Conclusions. The change in depression levels after art therapy intervention is statistically significant (p<0.05). The change in anxiety levels after art therapy intervention is not statistically significant (p>0.05). The shift of the drawings is from abstract to specific iconography. The formal motifs of the drawings become more detailed and their type of representation become more varied; the depiction of the objects have become more integrated in the composite space, and the composition become more open; the paintings became more artistic, and the color range became wider. The psycho-emotional state of the subjects in the sessions varied from detachment, withdrawal, hiding, fear of looking at oneself, to opening up, trying to notice and make sense of all one's own negativity, to manage negative emotions and to project one's future.                       Keywords: art therapy, woman suicide, anxiety, depression.